Isothermal Decay Analysis of Thermoluminescence Peaks of Quartz for Kinetic Parameter Determination - Sahib Mammadov; Muslim Gurbanov; Aqshin Abishov; Ahmad Ahadov (East European Journal of Physics, 2024)
This study delves into the intricacies of isothermal decay analysis applied to thermoluminescence (TL) peaks, focusing on determining kinetic parameters. The study challenges the conformity of the trap responsible for the ITL signals to first, second, or general-order kinetics, supported by the non-conforming decay pattern and the inference of two overlapping first-order TL peaks. This work enhances the understanding of TL peaks and establishes a reliable methodology for characterizing luminescence mechanisms in materials, contributing to advancements in luminescence dosimetry research. These observations lead to the conclusion that the TL data originates from more than one trap, and based on existing literature, it is inferred that there are two overlapping first-order TL peaks. The investigation involves the consideration of isothermal decay data at distinct temperatures (T = 250, 260, 270, 280, and 290°C) and explores challenges associated with achieving precise linear fits for different kinetic order values (b). The nature of decay is interpreted based on the monomolecular theory, suggesting adherence to a first-order process. ITL curves were deconvoluted into two exponential decay curves. The slopes of the regression lines provide activation energy (E) values for curve1 and curve2, respectively: E1 = 0.99±0.16 eV and E2 = 1.32±0.18 eV. The frequency factor (s) is determined from the intercept of the regression line: s1 = 1.32×108 s−1 and s2 = 1.77×1012 s−1.